Life Course Pathways of Adverse Childhood Experiences Toward Adult Psychological Well-Being: A Stress Process Analysis - Nurius, Paula S. (Child Abuse Negl, 2015)
Growing evidence suggests that toxic stressors early in life not only convey developmental impacts but also augment risk of proliferating chains of additional stressors that can overwhelm individual coping and undermine recovery and health. Examining trauma within a life course stress process perspective, we posit that early childhood adversity carries a unique capacity to impair adult psychological well-being both independent of and cumulative with other contributors, including social disadvantage and stressful adult experiences. This study uses data from a representative population-based health survey (N = 13,593) to provide one of the first multivariate assessments of unique, cumulative, and moderated effects of adverse childhood experiences (ACEs) toward explaining 3 related yet distinct measures of adult mental health: perceived well-being, psychological distress, and impaired daily activities. Results demonstrate support for each set of hypothesized associations, including exacerbation and amelioration of ACEs effects by adult stress and resilience resources, respectively. Implications for services and future research are discussed.